Sistema de control interno para bienes de larga duración del Consejo Nacional Electoral de la provincia del Carchi. - Narváez Mora, Alexandra Janeth (2015)
Today institutions whether public or private use of fixed assets or durable goods ¡is essential for the development of business activities should therefore establish clear Procedures thereof to be controlled and evaluated in a manner that allows identify errors early and subsequent handling goods especially in public institutions enables compliance with the regulations for the administration of these, since they represent a significant part of the entities and require full responsibility for their use custody and preservation from the highest authority until the last of officials, In this thesis has been used methods of quantitative and qualitative research, as well as theoretical and empirical research methods were applied throughout the thesis and the use of techniques and instruments that contribute to the collection of valid information, which is used for the proposed approach to the problem identified in the state, Subsequently presentation of an Internal Control System for Real Long Duration in the National Electoral Council of the province of Carchi with which it is intended to improve the management and control of these by developing procedures and instruments suitable for the reception is performed But custodian allocation, coding, physical verification, transfer, prior to the low discharge, and revaluation of assets by determining responsibilities to officials who are involved in their Management based on the regulations issued.